The Effect of Work Discipline and Compensation on Employee Performance at the Waste Handling Unit (UPS) of the Setiabudi Reservoir Water Agency, South Jakarta - Meivina Kusuma Darminto; Dewi Kurniawati (Publikasi Indonesia, 2026)
Employee performance is an important factor in supporting the effectiveness of public services, especially in the hygiene and environmental management sector which has a high level of risk and field workload. The Waste Management Unit (UPS) of the Setiabudi Reservoir Water Agency has a strategic role in maintaining the cleanliness of the reservoir and flood control in the South Jakarta area, so it requires human resources who have high work discipline and are supported by a fair and adequate compensation system. However, in practice, there are still various challenges related to discipline and perception of compensation that have the potential to affect employee performance. Therefore, this study aims to analyze the influence of work discipline and compensation on employee performance at the Setiabudi Reservoir Water Agency UPS. This study used a quantitative method with SPSS 27 analysis tools. Data was collected through the distribution of questionnaires to UPS employees of the Setiabudi Reservoir Water Agency as research respondents. The results of the study show that work discipline has a positive and significant effect on employee performance, which indicates that compliance with rules, punctuality, and work responsibility can improve the effectiveness and quality of performance. Thus, this study provides the implication that improving work discipline and improving compensation policies in a sustainable manner is a strategic step in improving employee performance and the quality of public services in the field of environmental management.